APB Online Workshop Series: English For University Professionals / Norhaslinda Hassan - Hassan, Norhaslinda (Academy of Language Studies, 2022)
APB Online Workshop Series: English For University Professionals marks the inaugural online workshop series initiated by the Academy of Language Studies, UiTM Cawangan Pulau Pinang. The first of its series entitled ‘Writing Error-Free Social Media Posts’ commenced the online workshop on 19 November 2021. Facilitators for this series were Dr. Rofiza Aboo Bakar, Maizatul Akmal Mohd Mohzan, Norhafizah Abdul Halil, Muhammad Aiman Abdul Halim Aiman, Rosmaliza Mohamed, led by Dr. Norhaslinda Hassan. It was a 2-hour session, which started at 3 p.m and ended at 5 p.m via Google Meet.